About criminal liability for atmospheric pollution - Koshkinbaeva, A.S.; Sydykova, L.Ch. (Bulletin of the Karaganda University “Law Series”, 2019)
In the article the author gives a criminal-legal characteristic of air pollution. Also analyzes the structure of specified criminal provisions, the provisions of sectoral legislation.During the study of judicial practice there is a low level of detection of criminal offenses characterized by violation of environmental requirements, including air pollution. Often there are difficulties in distinguishing the criminal case on the pollution of the atmosphere from such norms. It is known that the correct criminal assessment of criminal activity is carried out by establishment of signs of structure of a criminal offense. To ensure the correct differentiation of identical norms, the author proposes to proceed from the type of environmental requirements specified in the relevant criminal norm.However, in the process of systematization of environmental legislation based on codification in recent years, some environmental laws have been abolished, as a result of which the EC of Kazakhstan has not fully disclosed environmental requirements for certain natural resources, in particular atmospheric air. Therefore, the author notes the need to improve the issue of environmental requirements provided in the EC RK. To ensure the correct application of the law in cases of environmental criminal offenses, the author proposes in the regulatory resolution of the Supreme Court of Kazakhstan to specify what environmental requirements and (or) rules should have been observed in the implementation of economic and other activities, production, storage and use of environmentally hazardous substances, the Commission of other actions (water, hunting, felling of trees and shrubs, etc.), as well as what regulatory legal acts these requirements and rules are established, ie. specify the name of the regulatory act and the article number.